Preparation and Characterization of Antioxidant Peptides from Carrot Seed Protein - Nanhui Ye; Pei Hu; Shuli Xu; Minming Chen; Shaoyun Wang; Jing Hong; Taotao Chen; Tiantian Cai (Journal of Food Quality)
Carrot is a very popular vegetable and used for culinary and cosmetic purposes. Carrot seeds can be used for treatment of hangovers and stimulating menstruation. In the present study, the carrot seed protein (CSP) extracted from carrot seed (Daucus carota L.) was hydrolysed by four proteases (papain, trypsin, neutrase, and alcalase). Alcalase hydrolysate exhibited the strongest DPPH radical-scavenging activity (DRSA). The optimum hydrolysis condition for the antioxidant peptide production from CSP was obtained using response surface methodology (RSM). The optimum condition was as follows: hydrolysis time of 3.50 h, substrate concentration of 52.8 g/L, and protease dosage of 419.36 U/g, under which DRSA of 82.46% at 2 mg/mL was obtained. The carrot seed protein hydrolysates (CSPHs) were separated using size exclusion chromatography in order to obtain peptides with stronger antioxidant activity. The hydrolysates were fractionated into four peaks, and fractions F3 and F4 with smaller molecular weight showed stronger antioxidant activity. These findings indicated that the success of RSM in optimizing the hydrolysis conditions and the further work in separation of antioxidant peptides in CSPH is feasible. The CSPH exhibites good antioxidant properties and can be used as useful ingredient in foods.